Metallomesogens with Luminescent Behaviour: Palladium Complexes Derived from Alkylamide Tetraarylporphyrins - Moura, Nuno M. M.
A series of meso-tetraaryl-substituted free-base porphyrins containing different numbers of alkyl amide chains with different lengths, as well as the corresponding palladium(II) and platinum(II) complexes, were prepared in good yields and were fully characterised. The crystal structure of the palladium(II) complex containing eight alkyl chains with five carbon atoms was unequivocally elucidated by means of single-crystal XRD studies. The thermal behaviour of the new compounds was studied by polarised light optical microscopy and differential scanning calorimetry. Porphyrins with eight terminal alkyl chains containing five and eight carbon atoms, and the corresponding palladium(II) complexes, behave as liquid-crystalline materials, exhibiting lamellar columnar mesophases at temperatures above 80 degrees C. The number of terminal alkyl chains and the palladium(II) metal centre play a key role in achieving mesomorphic behaviour.